PEGylated Nanographene Oxide in Combination with Near-Infrared Laser Irradiation as a Smart Nanocarrier in Colon Cancer Targeted Therapy - Milena Georgieva; Zlatina Gospodinova; Milena Keremidarska-Markova; Trayana Kamenska; Galina Gencheva; Natalia Krasteva (MDPI AG, 2021)
Anti-cancer therapies that integrate smart nanomaterials are the focus of cancer research in recent years. Here, we present our results with PEGylated nanographene oxide particles (nGO-PEG) and have studied their combined effect with near-infrared (NIR) irradiation on low and high invasive colorectal carcinoma cells. The aim is to develop nGO-PEG as a smart nanocarrier for colon cancer-targeted therapy. For this purpose, nGO-PEG nanoparticles' size, zeta potential, surface morphology, dispersion stability, aggregation, and sterility were determined and compared with pristine nGO nanoparticles (NPs). Our results show that PEGylation increased the particle sizes from 256.7 nm (pristine nGO) to 324.6 nm (nGO-PEG), the zeta potential from −32.9 to −21.6 mV, and wrinkled the surface of the nanosheets. Furthermore, nGO-PEG exhibited higher absorbance in the NIR region, as compared to unmodified nGO. PEGylated nGO demonstrated enhanced stability in aqueous solution, improved dispensability in the culture medium, containing 10% fetal bovine serum (FBS) and amended biocompatibility. A strong synergic effect of nGO-PEG activated with NIR irradiation for 5 min (1.5 W/cm−2 laser) was observed on cell growth inhibition of low invasive colon cancer cells (HT29) and their wound closure ability while the effect of NIR on cellular morphology was relatively weak. Our results show that PEGylation of nGO combined with NIR irradiation holds the potential for a biocompatible smart nanocarrier in colon cancer cells with enhanced physicochemical properties and higher biological compatibility. For that reason, further optimization of the irradiation process and detailed screening of nGO-PEG in combination with NIR and chemotherapeutics on the fate of the colon cancer cells is a prerequisite for highly efficient combined nanothermal and photothermal therapy for colon cancer.